Synergistic effects of glyphosate- and 2,4-D-based pesticides mixtures on Rhinella arenarum larvae - Peluso, Julieta (2022)
Glyphosate and 2,4-D are two herbicides commonly used together. Since there is little information about the interactions between these pesticides, the aim of this study was to evaluate the single and joint lethal toxicity of the glyphosate-based herbicide (GBH) ATANOR® (43.8% of glyphosate, isopropylamine salt) and the 2,4-D-based herbicide (2,4-DBH) Así Max 50® (602000 mg/L of 2,4-D) on Rhinella arenarum larvae. Equitoxic and non-equitoxic mixtures were prepared according to the recommendation for their combination and analyzed with a fixed ratio design at different exposure times and levels of lethality (LC10, LC50, and LC90). GBH (504h-LC50=38.67 mg ae/L) was significantly more toxic than 2,4-DBH (504h-LC50=250.31 mg ae/L) and their toxicity was time-dependent. At 48h, the equitoxic mixture toxicity was additive and from the 96h was antagonistic at LC10 and LC50 effect level. The non-equitoxic mixture toxicity was additive at LC10 effect level from the 48h to the 168h, and synergistic from the 240h. At LC50 and LC90 effect level, the mixture interaction resulted synergistic for all exposure times. This is the first study to report the synergistic interactions between GBH and 2,4-DBH on amphibians, alerting about its negative impact on aquatic ecosystems.